How to safely and sustainably reorganise a large general radiography service facing the COVID-19 pandemic. Issue 4 (November 2020) - Sim, W.Y.; Chen, R.C.; Aw, L.P.; Abu Bakar, R.; Tan, C.C.; Heng, A.L.; Ooi, C.C.
Abstract: Objectives: This paper aims to share our experience in reorganising our general radiography service during the coronavirus disease (COVID-19) pandemic from the viewpoint of a large tertiary referral medical centre. Key findings: Re-organization of the radiography workforce, patient segregation, and modification of routine radiographic practices are key measures to help radiographic services deal with the COVID-19 pandemic. Specific emphasis on deploying more mobile radiographic units, segregating equipment, developing consistent image acquisition workflows, and strict adherence to infection control protocols are paramount to minimize the possibility of in-hospital transmission and ensure a safe environment for both patients and staff. Streamlining communication channels between leadership and ground staff allows quick dissemination of information to ultimately facilitate safe provision of services. Conclusion: COVID-19 has drastically altered the way general radiography teams provide services. The institution of several key measures will allow hospitals to safely and sustainably provide radiographic services. To date, there have been zero incidences of radiographer healthcare worker transmission within our institution during the course of work. Implication for practice: Radiographers are facing the challenge of providing high-quality services while simultaneously minimizing pathogen exposure to staff and patients. Our experience may lend support to other radiographic services responding to the COVID-19 outbreak and serve as a blueprint for future infectious disease outbreak contingency plans.